An integrated watershed and water quality modeling system to study lake water quality responses to agricultural management practices. (June 2023) - Chao, Xiaobo; Witthaus, Lindsey; Bingner, Ronald; Jia, Yafei; Locke, Martin; Lizotte, Richard
Abstract: This paper presents a technical approach to link a watershed model and surface water quality model to study the effects of agricultural conservation practices on the water quality of a receiving water body. The AnnAGNPS watershed model was applied to simulate runoff and loads of sediment and nutrients into Beasley Lake. The simulated results were used as boundary conditions for CCHE-WQ water quality model to simulate the concentrations of water quality constituents in the oxbow lake. In this model, the interactions between sediment and water quality constituents were considered. This integrated modeling system can be used to simulate flow, sediment and nutrient processes in both the watershed and waterbody systematically. Two modeling were calibrated and validated using measured data in Beasley Lake Watershed. The validated modeling system was applied to analyze the effects of cropping and tillage systems on the water quality of the receiving water body. Highlights: An integrated modeling system was developed to link AnnAGNPS and CCHE-WQ to study water quality throughout the entire watershed. The models were calibrated and validated using measured data in Beasley Lake Watershed. The modeling system was applied to analyze the lake water quality response to cropping and tillage systems. The modeling system can be used to analyze the effects of agricultural practices on watershed runoff and lake water quality. The integrated modeling system can be used to evaluate the effectiveness of conservation practices on water quality improvement.